2021
DOI: 10.3390/nu13082846
|View full text |Cite
|
Sign up to set email alerts
|

Government Options to Reduce the Impact of Alcohol on Human Health: Obstacles to Effective Policy Implementation

Abstract: Evidence for effective government policies to reduce exposure to alcohol’s carcinogenic and hepatoxic effects has strengthened in recent decades. Policies with the strongest evidence involve reducing the affordability, availability and cultural acceptability of alcohol. However, policies that reduce population consumption compete with powerful commercial vested interests. This paper draws on the Canadian Alcohol Policy Evaluation (CAPE), a formal assessment of effective government action on alcohol across Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Two high quality country case studies reported that delayed action can stem from alcohol not being perceived as a national priority [111,112]. Countries ran into difficulties when specific directions were not provided about how all information should be presented on labels (size, font, position, wording etc) or where WHO recommendations were not followed [113]. We note that Libya has implemented all alcohol Best Buy policies.…”
Section: Plos Global Public Healthmentioning
confidence: 89%
“…Two high quality country case studies reported that delayed action can stem from alcohol not being perceived as a national priority [111,112]. Countries ran into difficulties when specific directions were not provided about how all information should be presented on labels (size, font, position, wording etc) or where WHO recommendations were not followed [113]. We note that Libya has implemented all alcohol Best Buy policies.…”
Section: Plos Global Public Healthmentioning
confidence: 89%
“…Governments and governmental organizations seem to consider that the pleasure is worth the pain. As Stockwell and colleagues point out, it is possible to provide very specific and detailed advice to governments regarding the public health consequences of policy decisions in such concrete terms as how many people will become ill, injured or die prematurely from alcohol-related reasons if policy X or Y is not introduced [13]. Yet, almost all countries fall far short of implementing effective public health policies to reduce the harm done by alcohol [13].…”
mentioning
confidence: 99%
“…As Stockwell and colleagues point out, it is possible to provide very specific and detailed advice to governments regarding the public health consequences of policy decisions in such concrete terms as how many people will become ill, injured or die prematurely from alcohol-related reasons if policy X or Y is not introduced [13]. Yet, almost all countries fall far short of implementing effective public health policies to reduce the harm done by alcohol [13]. Further, despite alcohol being a carcinogen, [4,5], at least in Europe, health warning labels are notable by their absence [14].…”
mentioning
confidence: 99%
See 2 more Smart Citations